Los Dialectices libri quatuor de Juan Luis Vives: una obra desconocida - Labado Santiago, José María; Benedí Andrés, Concepción; Martín Contreras, Luis; Mañas Núñez, Manuel (1994)
Los Díalectices librí quatuor (París, 1550), obra póstuma de Vives, constituyen una lógica elemental, fácil y funcional. Entiende la lógica como un ars sermocinalis, esto es, como un instrumento útil para el discurso. Debió de ser escrita entre 1512-1519. Es posible que sea una obra espuria.
Vives’s posthumous Díalectices líbrí quatuor (Paris, 1550) was abasic, but rather, useful treatise for student. He shows that logie for him was an ars sermocinalis, that is, a useful instrument for discourse. 1 suggest that the book, though published at the abore date, was written somewhat earlier, between 1512-1519. And furthermore, it might also be a spurious work, wrongly attributed to Vives’ pen.
Keywords: Vives, Juan Luis, -- 1492-1540